2018
DOI: 10.29244/jai.2018.6.2.133-148
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Nilai Tambah Pelaku Rantai Pasok Organisasi Jaringan Madu Hutan Sumbawa (Jmhs) Menggunakan Metode Hayami

Abstract: <em>This study was aimed to analyze the added value in the supply chain of forest honey at Jaringan Madu Hutan Sumbawa (JMHS) organization.  The respondents in this study are 30 honey hunter, 2 group leader, 2 JMHS cooperative and 1 marketing outlet Rumah Madu. Quantative descriptive analysis method was used to analyze the added value by using Hayami’s method (1987). The results from this study were the added value of forest honey from Madu Hutan Lestari cooperation is 0.5 persen highest than other chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
4
1
1
Order By: Relevance
“…This indicates that the distribution activity at the fried duck restaurant was better compared to other activities by other distribution participants in the supply chain. The result of supply chain analysis in this study is different from the supply chain analysis of honey products by Qashiratuttarafi (2018), which showed that the highest value-added was obtained by packaging and distribution activity by the marketing outlet (supplier) with the added value ratio at 64%.…”
Section: Added Value At Fried Duck Restaurantcontrasting
confidence: 90%
“…This indicates that the distribution activity at the fried duck restaurant was better compared to other activities by other distribution participants in the supply chain. The result of supply chain analysis in this study is different from the supply chain analysis of honey products by Qashiratuttarafi (2018), which showed that the highest value-added was obtained by packaging and distribution activity by the marketing outlet (supplier) with the added value ratio at 64%.…”
Section: Added Value At Fried Duck Restaurantcontrasting
confidence: 90%
“…At the same time, fish cultivators have the least added value, which is also in accordance with research stating that farmers obtain economic added value. smaller than that of other collectors [21]. Previous research stated that the greatest added value is in industry.…”
Section: Introductionmentioning
confidence: 90%
“…The obtained data were then processed and analyzed using value chain analysis and supply chain analysis methods [8]. The calculation using Hayami's method was aimed to compare value-added weights received by each supply chain actor [9]. Meanwhile, the production method/flow will be analyzed descriptively using a SWOT analysis approach (Table 4).…”
Section: Data Analysis Methodsmentioning
confidence: 99%